(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study focuses on the subject of the sun-breakers design to rationalize building energy requirement for the thermal comfort of building occupants. Though many scientific studies and some local studies had taken up the subject of sun-breakers design, they have not addressed the extent to which the sun-breaker design depth affects the building energy requirements in Baghdad city. There is no completely comprehensive and exact research of standards for the effect of the depth of the sun-breakers design on the building energy requirements in Baghdad city. Thus, we have indicated goal of this research as "determine the impact of the sun-breakers design depth on the building energy requirements in Baghdad city." To achieve these goals we had followed the procedures below: In order to achieve this, the following methods are required: Indicating the theoretical framework of the sun-breakers design to recognize its importance and role in energy conservation in buildings depending upon previous available studies. Determination of the influence of the sun-blockers design depth on the requirements of building energy exchange through the study of the building plot (test sample) and using a computer program (PHPP) to measure the energy exchange requirements and then analyze them to reach the results. Finally, conclusions were present, which cover the aim of the research.